Deciphering the near-field response with the far-field wavelength-scanned SERS spectra of 4-mercaptopyridine adsorbed on gold nanocolloidal particles entrapped in Langmuir Reverse Schaefer film of 5CB liquid crystal molecules. Issue 16 (9th April 2020) - Das, Sumit Kumar; Bhattacharya, Tara Shankar; Chowdhury, Joydeep
Abstract : Wavelength-scanned SERS spectra of 4-mercaptopyridine molecule adsorbed on gold nanoparticles immobilised in a Langmuir Reverse Schaefer film of 5CB molecules. Abstract : Herein, we have reported the wavelength-scanned (WS) SERS spectra of 4-mercaptopyridine molecules (4-MPy) adsorbed on gold nanoparticles immobilised in a Langmuir Reverse Schaefer (-RSh) film matrix of 5CB molecules. The WS-SERS spectral profile exhibited an increment in the intensity of the enhanced Raman bands of 4-MPy with an increase in the wavelength of the excitation laser source. The rationale behind the experimental observations was supported by the simulated extinction spectra and the enhancement factor measurements of the modelled systems using the T -matrix formalism. The SERS intensity fluctuations in the band located at 1000 cm −1 for the 4-MPy molecule, as obtained from three different locations in the -RSh film substrate, were also analyzed. Surprisingly, depending on the spatial locations of the substrates, the intensity fluctuations of the abovementioned band exhibit both Poisson and Gaussian distributions but the maximum number of probe molecules that can reside in the scattering areas under investigation cannot exceed sixteen. These observations suggest that the origin of SERS from single/few molecules or from the ensemble-averaged system cannot be inferred from the statistical distributions of the Raman intensity fluctuations. The present experimental observations also revealed the relation between the near-field plasmonic behaviors of the substrate with the corresponding far-field SERS spectra of the 4-MPy molecule.